Synergistic absorbents based on SnFe2O4@ZnO nanoparticles decorated with reduced graphene oxide for highly efficient dye adsorption at room temperature - Singh, Pawan Kumar (Royal Society of Chemistry, 2021)
Recently, adsorption techniques have emerged as practical and effective methods for removing organic dyes, dramatically extending practical capabilities for treating deleterious pollutants in wastewater. However, an urgent issue restricting the performance of these techniques is that no available absorbents that can be used to treat both cationic and anionic organic dyes have been made with simple and reliable methods until now. Herein, we report a green synthetic strategy for the preparation of SnFe2O4/ZnO nanoparticles decorated on reduced graphene oxide (rGO), exhibiting a remarkably large surface area (120.33 m(2) g(-1)). Substantial adsorption efficiency for removing MB dye was achieved, with 91.3% removal within 20 min at room temperature, and efficiencies of 79.6 to 92.8% are maintained as the pH conditions are varied from 3 to 11. Moreover, under mixed-dye conditions, involving MB, RhB, MO, RB5, and R6G organic materials, with dye concentrations ranging from 0.005 mM to 0.09 mM, an adsorption efficiency of above 50% can be reliably reached within 20 min. Such striking features can be interpreted as arising from a synergistic effect involving the hybrid composite based on a rGO matrix with negative charge and the dispersed SnFe2O4/ZnO nanoparticles with positive charge, additionally offering abundant adsorptive sites to allow reliable dye-adsorption kinetics.